Adsorption and time dependent fixation of uranium (VI) in synthetic and natural matrices - Ashry Abdelaal, Ahmed (2017)
Disposal of low level radioactive liquid waste to soil is commonly practiced. Therefore, sorption of uranium from aqueous solution and fixation of uranium into soil are processes which are crucial to the attenuation of uranium and protection of groundwater. Exposure of human populations is either by direct water consumption or through crop irrigation and transfer into the food chain. In this study a range of materials, including natural materials (e.g. biochar and the natural zeolites ‘Chabazite and Mordenite’) and the synthetic zeolite ‘Faujasite-X’, were investigated as potential adsorbents for UVI from aqueous solution. A range of experiments were carried out to investigate the efficacy of using these adsorbents to successfully adsorb and fix UVI from aqueous solutions. These included sorption and desorption experiments, quantifying time-dependent fixation of UVI and applying kinetic models of this process and measuring isotopically exchangeable UVI within adsorbent materials when possible. The factors affecting adsorption processes, such as solution pH, initially added UVI concentrations and adsorption contact time, were also investigated. Speciation of U in the solution phase was investigated using the Windermere Humic Aqueous Model (WHAM-VII). Saturation indices of potential solid phases were also configured using known solubility products and the free ion activities predicted from the speciation model, WHAM-VII. Mordenite zeolite showed a poor adsorption affinity for UVI as the solution pH was continuously buffered towards high pH values > 6.5 which favours UVI ion solubilisation as a result of uranyl carbonate complex formation. Uranium (VI) ion adsorption on chabazite at pH 4.7 at 20 oC was found to fit the Freundlich adsorption isotherm but the optimised equation parameters were unique for each contact time of 1, 5, 10, 20 and 30 days. The time-dependent fixation of UVI on chabazite was found to follow an irreversible first-order kinetic equation and an intraparticle diffusion model suggesting slow penetration of chabazite porous structure following initial surface adsorption. Isotopically exchangeable 238UVI (the E-value, UE) adsorbed on chabazite showed that > 65% of initially added UVI remained isotopically exchangeable. Faujasite-X also showed time-dependent fixation of UVI over 35 days of adsorption contact time at pH values 4, 5 and 6. The adsorption kinetics were best described by an irreversible first-order equation and a spherical diffusion model. Desorption trends showed that UVI adsorption into faujasite- X was almost wholly irreversible. Saturation indices calculated from the solubility products and free ion activities of constituent ions showed that the fixation of UVI was not controlled by the precipitation of any solid phase investigated at the studied range of pH values. Bone biochar, a by-product from the production of biofuel and syngas by gasification, was tested as a material for adsorption and fixation of UVI from aqueous solutions. A batch experiment was conducted to study the factors that influence the adsorption and time-dependent fixation on biochar at 20◦C, including pH, initial concentration of UVI and contact time. Uranium (UVI) adsorption was highly dependent on pH. However, it was found that UVI adsorption on biochar was high over a wide range of pH values, from 4.5 to 9.0, and adsorption strength was time-dependent over several days. The experimental data for pH> 7 were most effectively modelled using a Freundlich adsorption isotherm coupled to a reversible first order kinetic equation to describe the time-dependent fixation of UVI within the biochar structure. Desorption experiments showed that UVI was only sparingly desorbable from the biochar with time and isotopic dilution with 233UVI confirmed the low, and time-dependent, lability of adsorbed 238UVI. Below pH 7 the adsorption isotherm trend suggested that precipitation, rather than true adsorption, may occur. Across all pH values (4.5–9) measured saturation indices suggested precipitation was possible: autunite below pH 6.5 and swartzite, liebigite or bayleyite above pH 6.5 Another source of bone biochar with a fraction size of (20x 60 mesh) was investigated as candidate materials for soil remediation. Its ability both to adsorb uranium and to render it non-labile (i.e. chemically inactive) was tested by addition to a wide range of soils recently spiked with 238UVI and incubated under moist conditions. The overall aim was to recommend improved strategies for immobilisation of uranium in soils subject to application of low level radioactive waste solutions. Several measurements were made to assess possible reductions in U availability from biochar addition, including U solubility in 0.01 M Ca(NO3)2, exchangeability in 1 M Mg(NO3)2 solution and isotopic dilution with 233U and 236U. Results showed that 41.3 %, 27.6%, 28.9% and 31.7% were isotopically exchangeable on average for soil amended with 0%, 3%, 5% and 10% loading of biochar, but overall there appeared to be only marginal advantages in adding even large concentrations of biochar to soil. The major factor controlling U solubility, exchangeability and lability was soil pH and the pH value resulting from biochar, rather than the biochar itself. Therefore, while the use of biochar to effectively remove U from water is clear, its role in adsorbing U in the highly buffered soil environment is probably minimal.